2006
DOI: 10.1001/archopht.124.2.217
|View full text |Cite
|
Sign up to set email alerts
|

Memantine Protects Neurons From Shrinkage in the Lateral Geniculate Nucleus in Experimental Glaucoma

Abstract: To determine whether memantine as a treatment for glaucoma prevents neuron shrinkage in the lateral geniculate nucleus, the major target for retinal ganglion cells.Methods: Sixteen monkeys with right-eye unilateral experimental glaucoma for 14 months were studied and treated with memantine (n=9) or vehicle only (n=7). Left lateral geniculate nucleus relay neurons (layers 1, 4, and 6) were examined following parvalbumin immunolabeling. Cell body cross-sectional areas and neuron numbers were assessed using unbia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(44 citation statements)
references
References 40 publications
0
41
0
2
Order By: Relevance
“…Therefore, it is argued that the neuroprotective agents can be used in the therapy of glaucoma. A study, conducted by Yucel et al 21 on nine monkeys with experimentally created glaucoma, showed that the use of memantine, which is a NMDA receptor blocker, gave better statistically significant results when compared with controls in neuronal damage and neuron atrophy in the LGB region.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is argued that the neuroprotective agents can be used in the therapy of glaucoma. A study, conducted by Yucel et al 21 on nine monkeys with experimentally created glaucoma, showed that the use of memantine, which is a NMDA receptor blocker, gave better statistically significant results when compared with controls in neuronal damage and neuron atrophy in the LGB region.…”
Section: Discussionmentioning
confidence: 99%
“…It has, therefore, been desirable to develop treatment strategies by which the retina and optic nerve can be protected from degeneration by helping the retinal cells to survive even under difficult conditions. Recent studies have reported that substances such as ciliary neurotrophic factor, [3][4][5] brain-derived growth factor, 6 memantine, 7,8 and Ginkgo biloba may have a stabilizing or protecting effect on retinal cells in experimental conditions. [9][10][11][12][13][14][15][16][17][18][19][20][21][22] Particularly for Ginkgo biloba, potential antioxidant functions have been discussed to be helpful for impaired retinal cells such as Mü ller cells.…”
Section: Introductionmentioning
confidence: 99%
“…Memantine is used in the treatment of Parkinson’s disease, some types of movement disorders [19] and some dementia syndromes [20], and has recently been described as a potential treatment for glaucoma [21]. …”
Section: Discussionmentioning
confidence: 99%